ANALISIS EKONOMI MAKRO DAN KARAKTERISTIK PERUSAHAAN TERHADAP SISTEM BAGI HASIL - Siti Fatimah; Nur Hayati; Ardi Hamzah (MediaTrend, 2013)
Shariah bank established to stabilize the inflation, whereas it interest may become tool to control inflation. On the other hand, interest could caused high rate inflation. Normally this type of research is conducts in the field of commercial or regular bank, this time the researcher tried to apply it on the shariah bank. The researcher use two common shariah bank in Indonesia; Bank Syariah Mandiri and Bank Muamallat. The reason why the researcher use those two, because they are recognized by most people in Indonesia.This research aim is to test the macro economics impact on the banking sharing system, to test the implication on company characteristics towards banking sharing system, and to test both impact and implication of banking sharing system on macro economics and company characteristics.Quantitative descriptive is used on this research with using survey method and literature reviews in helping on the data collection then its analyzed with SPSS program. The research hyphothesis shows that macro economics and company characteristics impact and implication on banking sharing system were acceptable. And finally the result of this research could sumply conclude that (1) macroeconomics were significantly impacted on the banking system whereas PDB and unemployment not (or shows negative impact), (2) company characteristics were significantly impact on the banking system whereas ROA and PER shows negative impact and (3) macroeconomics and company characteristics have both no impact on the banking system, it proves by the absence of t-value and F-value.